Medieval Sicily and Southern Italy in Recent Historiographical Perspective - Davis-Secord, Sarah (History compass, 2010)
Sicily and southern Italy during the Middle Ages have been a neglected area of study for many years, primarily due to the general belief that the area fell into decline after the ‘fall’ of Rome. Recently, however, there has been growing interest in the Muslims of medieval Sicily and Italy, as well as the Jewish and Greek populations that lived under Latin Christian rule for many centuries. There has also been a rise in scholarship on the medieval Mediterranean region as a whole, which has caused a re-evaluation not only of the role and importance of the Mediterranean world, but also of how the medieval European system worked, how Latin Christendom related to the Muslim states on its southern borders, and what roles Muslim cultures and settlements played in the development of Italy’s society.